Factors influencing the distribution of 223Ra and 224Ra in the coastal waters off Tanggu and Qikou in Bohai bay. (15th October 2015) - Tang, Guoqiang; Yi, Lixin; Liu, Lingling; Cheng, Xiaoqing
Abstract: The naturally occurring 223 Ra and 224 Ra isotopes have become an established tool for investigating water mixing and submarine groundwater discharge (SGD). In this paper, we used the radium delayed coincidence counter (RaDeCC) to measure 223 Ra and 224 Ra activities, the distributions of 223 Ra and 224 Ra in two coastal waters with different hydrographical conditions and its influence factors were explored in Bohai bay. The results indicated that the Ra concentration was constrained by coastal land use patterns, the type of water and the geochemical environment. The Ra concentrations in groundwater and beach water were generally higher than the Ra concentrations in offshore waters. In the highly urbanized and industrialized Tanggu area, both of 223 Ra in coastal water (average 3.74 dpm/100 L) and 224 Ra (average 41.3 dpm/100 L) were lower than that in the undeveloped Qikou area (average 9.65 dpm/100 L and 148.9 dpm/100 L for 223 Ra and 224 Ra, respectively). Urbanization and Marine reclamations have modified local hydrogeological conditions, and then reduced SGD fluxes. Human activities have poured much more contaminants into coastal oceans and changed local aqueous environments, thus resulted all chemical compositions were richer in the urbanized coastal waters. With respect to the relationships between radium and the chemical compositions of the waters, radium was negatively related to salinity, nitrate and sulfate but was positively related to the concentration of cations such as calcium and magnesium. The apparent residence ages and SGD fluxes were also estimated from the radium distributions. There were more SGD fluxes into the coastal water off Qikou (9.88×10 7 m 3 /d) than into the water off Tanggu (1.22×10 7 m 3 /d). Highlights: The differences of Radium isotope distributions were observed in two coastal waters in Bohai bay. Land use patterns and marine reclamations have changed local geochemical conditions and chemical characteristics of water body. Ion strengths and cations concentration condition are important factors influencing Radium distributions in each region. Residence ages and SGD fluxes were estimated and indicated there were more SGD fluxes in Qikou coastal zone.